2016
DOI: 10.1016/j.nlm.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of basal forebrain cholinergic neurons in fear and extinction memory

Abstract: Cholinergic input to the neocortex, dorsal hippocampus (dHipp), and basolateral amygdala (BLA) is critical for neural function and synaptic plasticity in these brain regions. Synaptic plasticity in the neocortex, dHipp, ventral Hipp (vHipp), and BLA has also been implicated in fear and extinction memory. This finding raises the possibility that basal forebrain (BF) cholinergic neurons, the predominant source of acetylcholine in these brain regions, have an important role in mediating fear and extinction memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 193 publications
(358 reference statements)
1
65
1
1
Order By: Relevance
“…Given that the basal lateral amygdala (BLA) appears to receive the densest cholinergic innervation of any structure besides the striatum, and cholinergic input to the BLA exerts an important influence on acquisition and retention of emotional memories (Knox, 2016), detailed single neuron mapping of the cholinergic neurons that project to the amygdala should be very revealing.…”
Section: Cholinergic Neurons and Cholinergic Signaling Mechanisms mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the basal lateral amygdala (BLA) appears to receive the densest cholinergic innervation of any structure besides the striatum, and cholinergic input to the BLA exerts an important influence on acquisition and retention of emotional memories (Knox, 2016), detailed single neuron mapping of the cholinergic neurons that project to the amygdala should be very revealing.…”
Section: Cholinergic Neurons and Cholinergic Signaling Mechanisms mentioning
confidence: 99%
“…Cholinergic signaling specifically within the amygdala is vital for encoding emotionally salient memories (Fig 2; Knox, 2016). Optogenetic stimulation of cholinergic signaling in the amygdala strengthens emotionally salient memories, and optogenetic inhibition weakens them: both nAChRs and mAChRs appear to be involved (Jiang et al, 2016).…”
Section: Cholinergic Signaling and Circuits Involved In Attention mentioning
confidence: 99%
“…cBF neurons, through their release of acetylcholine, have been implicated in a wide range of cognitive processes and behaviours, including attention, fear-related processes and reward-mediated behaviour, addiction, memory updating, extinction and renewal [57][58][59][60][61]. Much of the early research that revealed the role of these neurons in the behavioural outcomes used lesioning methods, in which a saporin-conjugated p75 NTR -specific antibody was used to create a lesion that was specific to cBF neurons [62].…”
Section: The Function Of Adult Cbf Neurons Cbf Neuronal Effects On Bementioning
confidence: 99%
“…Depending on the behavioral paradigm, nAChRs in different brain regions of the network encoding and expressing fear memories mediate the effects of nicotine. Hippocampal nAChRs are modulated by exogenous nicotine in contextual fear conditioning and contextual fear extinction memory, although regulation by cholinergic neurons projecting to BLA appears to be essential for contextual extinction (Knox, ). The acquisition and expression of cue‐conditioned fear memory also involve cholinergic regulation of BLA neurons by nAChRs (Duvarci & Pare, ; Jiang et al., ); yet, systemic nicotine does not modulate conditioning in this fear paradigm (Gould & Leach, ), although BLA circuit activity is affected by nicotine in vitro (Jiang & Role, ).…”
Section: Regulation Of Fear and Anxiety By Nicotine Nachrs And Bla mentioning
confidence: 99%